(untitled) (Research, Society and Development, 2025)
The study aimed to evaluate the influence of chest drainage on the respiratory and motor functionality of patients over the days, analyzing possible deficits associated with the procedure. For this purpose, a prospective longitudinal study with a quantitative approach was conducted, including patients admitted to the University Hospital of Western Paraná, who underwent closed chest drainage. The sample consisted of 12 patients, who were evaluated at two moments: in the first 24 hours after insertion of the drain and on the fourth day of hospitalization. The variables analyzed included respiratory muscle strength (PIMAX and PEMAX), hand grip strength, shoulder range of motion (goniometry), thoracic mobility (cirtometry) and pain perception (VAS). The results showed that, although there was no statistically significant difference in respiratory muscle strength, dynamometry and goniometry over the days, the values remained below the normative references. Pain showed a significant reduction (p=0.01) between assessments, and thoracic mobility showed a significant improvement in cirtometry (p=0.02), indicating an increase in lung expansion. It is concluded that thoracic drainage impacts respiratory and motor function, with a reduction in muscle strength and range of motion. Despite the lack of statistical significance in some variables, the differences in relation to the reference values suggest the need for early physiotherapy monitoring. The study highlights the importance of future investigations on the subject.